MAINTENANCE OF SOCIAL AND PEDAGOGICAL SPACE OF HIGHER EDUCATION INSTITUTION AND DEVELOPMENT OF COMMON CULTURAL COMPETENCES - Tatyana Lvovna Stenina (Sovremennye Issledovaniâ Socialʹnyh Problem, 2015)
The purpose of research work – search of new ways of educational work, corresponding to requirements of federal state educational standards of higher education about formation of common cultural competences. The author suggests to use a method of social design for the solution of a task. The maintenance of social and pedagogical space of higher education institution is a complex of socially important ideas, projects and innovations. Participation in projects will allow students to seize competences which labor market demands. The author gives useful examples of use of design technologies for application in educational work of higher educational institutions.